ANALISIS MISKONSEPSI TERHADAP MATERI BANGUN DATAR DALAM PEMBELAJARAN MATEMATIKA KELAS IV SD NEGERI 15 LUBUKLINGGAU - Riska Paramita; Drajat Friansah; Riduan Febriandi (Primary Education Journal Silampari (PEJS), 2021)
Abstract: This research aims to determine what misconceptions arise in students and the factors that cause misconceptions in flat-building material in the fourth grade students of SD Negeri 15 Lubuklinggau. Subjects of the research were the fourth grade students of SD Negeri 15 Lubuklinggau with a total of 19 students. This type of research is qualitative descriptive with data collection techniques, namely observation, interviews, documentation and execution of test questions. The data analysis technique used is qualitative. The results showed that the misconceptions that emerged were theoretical misconceptions, classification misconceptions and correlational misconceptions. Misconceptions experienced by students are due to several factors, namely from the aspects of students and aspects of teachers as well as parents of students. Keywords: Analysis, Misconception, Flat Build, Mathematics.